ANALISIS PRIORITAS INVESTASI KELUARGA TENAGA KERJA INDONESIA (TKI) DI KECAMATAN BABADAN KABUPATEN PONOROGO - Choirul Hamidah; Umi Farida (AKUNTANSI DEWANTARA, 2017)
The study " Analysis of Family Investment Priorities TKI In District Babadan Ponorogo " This will be done in the District Babadan Ponorogo using rensponden TKI / TKW or family.This study uses a quantitative approach with a Case Study Diskriptif format because the population is so large that researchers used a sample to obtain research data . Total sample of 30 comprised of TKI / TKW and families who live in the District of Babadan especially those who have worked more than five years from various countries of destination. The survey results revealed that out of a total investment of family labor migrants in District Babadan choosing the form of investment in property (farmland , houses , stores) as much as 58 % , investments in the form of ownership of motor vehicles and cars (22 %) , deposits ( 11 % ) , Gold and other jewelry ( 5 % ) , and foreign currency ( 0.5 % ) , others 3.5% . The reasons for the selection of such investments , the investment risk is considered low , on the skills , local market potential and experience of migrant workers over the years.Â Keywords:Â  Priority , Investment, Indonessian worker (TKI)